Cultivating Mindfulness to Raise Children Who Thrive Why Human Connection from Before Birth Matters - Sansone, Antonella (London : Routledge, 2020)
Cultivating Mindfulness to Raise Children Who Thrive introduces an expanded view of human development and health, which begins before conception and moves through pregnancy, early childhood and adulthood. This book is a call for all prenatal and perinatal professionals and policy makers to appreciate indigenous ways of knowing, being and doing and integrate them with scientific evidence in the care of expectant parents and their babies. It explains how this could also tackle pressing social issues facing the modern world and favour social innovations through a revaluation of preconception, pregnancy, birth and childcare practices. Sansone presents the reader with scientific discoveries of epigenetics, interpersonal neuroscience, quantum physics,attachment, anthropology, prenatal and perinatal psychology and mindfulness, which interestingly resonate with the intuitions of primal wisdom. The book will be of interest to clinicians, policy makers, researchers, parents,and those interested in the prenatal and perinatal roots of human development and well-being.
Toward a New Paradigm of Human Development and Health; 1 Wisdom: the path to unleashing human nature and wellbeing; 2 The human work of art; 3 Integrating primal wisdom with modern Western Worldview; 4 Raising children towards wisdom; 5 The art and science of mindfulness; 6 Transformation of human traits and being; 7 Connection and Empathy: Enhancing Pre and Perinatal Healthcare Professionals' Interpersonal Skills; 8 ;Why maternal and paternal mental health and wellbeing matter; 9 Acknowledging the Intersubjective Reality; 10 A mindfulness relationship-based model to support maternal mental health and the mother-baby relationship in pregnancy and beyond birth; 11 Visioning the future; Afterword
OCLC-licensed vendor bibliographic record.
Keywords: Mindfulness (Psychology); Prenatal influences; MEDICAL / Nursing / Maternity, Perinatal, Women's Health; PSYCHOLOGY / Mental Health; PSYCHOLOGY / Psychotherapy / Couples & Family